(untitled) (Journal of Pharma Insights and Research, 2024)
Distillation processes play a pivotal role in the pharmaceutical industry for the purification of active pharmaceutical ingredients (APIs), intermediates, and solvent recovery. This summary explores the fundamental principles governing distillation, including mass transfer and phase equilibrium concepts. It delves into various distillation methods employed in pharmaceutical engineering, encompassing fractional distillation, azeotropic/extractive distillation, steam distillation, vacuum distillation, membrane distillation, and molecular distillation. Recent advancements in distillation technology, such as process intensification, miniaturization, and integration with other separation processes, are highlighted. The current state of distillation in pharmaceutical engineering is discussed, addressing regulatory considerations, solvent selection, and recovery challenges. Future prospects emphasize the need for energy-efficient and sustainable processes, advanced distillation technologies, process modeling and optimization, continuous manufacturing integration, and interdisciplinary collaboration. These efforts aim to drive innovation and address the evolving needs of the pharmaceutical industry, ensuring the continued importance of distillation in the purification and separation of pharmaceutical compounds